2015
DOI: 10.1080/14786419.2015.1055744
|View full text |Cite
|
Sign up to set email alerts
|

A new steroidal glycoside fromCorypha talieraRoxb., a globally endangered species

Abstract: A new steroidal glycoside, β-sitosterol-3-O-α-L-rhamnopyranosyl-(1→4)-β-D-xylopyranosyl-(1→4)-β-D-glucopyranosyl-(1→4)-β-D-glucopyranoside was isolated from the methanol extract of the pericarp of Corypha taliera Roxb. The reversed-phased HPLC analysis of the methanol extract of the pericarp of C. taliera Roxb. (Talipalm), a rare species of Arecaceae family, afforded a new steroidal glycoside, β-sitosterol-3-O-α-L-rhamnopyranosyl-(1→4)-β-D-xylopyranosyl-(1→4)-β-D-glucopyranosyl-(1→4)-β-D-glucopyranoside (1). T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was first identified by William Roxburgh in 1819 and found to be endemic in Bengal. It is also reported as an endangered species in the whole world (Shoeb et al, 2015). The last specimen of the plant was standing within the campus of the University of Dhaka, Bangladesh which was found to extinct in 2010 after one time flowering and fruiting (Basu and Chakraverty1994;Khan et al, 2001;Shoeb et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was first identified by William Roxburgh in 1819 and found to be endemic in Bengal. It is also reported as an endangered species in the whole world (Shoeb et al, 2015). The last specimen of the plant was standing within the campus of the University of Dhaka, Bangladesh which was found to extinct in 2010 after one time flowering and fruiting (Basu and Chakraverty1994;Khan et al, 2001;Shoeb et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Significant evidence regarding economic value, botanical information including panicle initiation, flowering and fruiting as well as biochemical composition of flowers and fruits of the plant have been recorded primarily (Shoeb et al, 2015;Khondker et al 2010). Recently, phytochemical screening revealed that the unripe fruits contain significant bioactive molecules including βsitosterol, β-amyrin, betulinic acid, lupeol (Chowdhury et al, 2013), palmitic, myristic, linoleic, arachidic, stearic, lignoceric acids (Shoeb et al, 2013 and (Shoeb et al, 2015). Bioactivity assays of the extractives of the plant revealed its promising antioxidant and cytotoxic properties and mild to moderate activity against pathogenic microorganisms (Chowdhury et al, 2010).…”
Section: Introductionmentioning
confidence: 99%